Self-medication practice among preclinical university students in a medical school from the city of Pokhara, Nepal (Nepal Journal of Epidemiology, 2016)
Introduction: In developing countries like Nepal medicines can be acquired from the chemist's without of a prescription which sometime may have many drawbacks due to intake of excessive drugs without a proper diagnosis.  The primary objective of the study was to find out the pattern of self-medication practice among the preclinical medical students at Manipal College of Medical Sciences.Materials and Methods: This was a cross sectional study carried out using structured questionnaire at Manipal College of Medical Sciences, Pokhara, Nepal between November 2012- July 2014.Results: The overall response rate of this study was 95.31%. 81.35% of the students were practicing self-medication in this institution. Most common group of drugs that were consumed were antipyretics 31%, antibiotics 26.2%, analgesics 18.89%, antihistaminics 10.1% respectively. Paracetamol was the most common drug used for self-medication 31%, followed by Azithromycin 17.6% and combination of Paracetamol and Ibuprofen 15.6%, Cetirizine 8.6%, Amoxicillin 6.5%, Omeprazole 6.3%, Albendazole 3.3%, Mefenemic acid 2.8%, Cefpodoxime2% respectively. Conclusion: Medical student should be educated through awareness programme regarding pros and cons of self-medication practice and they should be motivated regarding the rationale use of antibiotics.